Modernising Indian Agriculture Report on the Intensive Agricultural District Programme (1960-68) Volume I - Planning Commission (Planning Commission, 1960)
This is the Fourth Evaluation Report of the Intensive Agricultural District Programme (IADP) to be made by the Expert Committee on Assessment and Evaluation. The First Report was made in October 1963 and covered the initial programme operations in the years 1961—63. A large part of that period was taken up with making preliminary arrangements and the launching of the programme. The Second Report was made in April 1966 covering the period from 1961 to 1965. This gave two more years of operating experience with the programme. A significant finding of that report was that the full impact of the IADP would take a much longer time than the five years contemplated in its original formulation.
Expert Committee on Assessment and Evaluation Ministry of Food, Agriculture, Community Development & Cooperation (Department of Agriculture)